Use of a Retrospective Methodology to Examine the Process of Care Surrounding Serious Medical Events in HIV-Positive Patients: A Feasibility Study. (24th August 2019) - Pool, Erica R M; Cooper, Vanessa; Youssef, Elaney; Wright, Juliet; Skittrall, Jordan; Blach, Ola; Fisher, Martin; Smith, Helen
Introduction: Comorbidities are increasingly common among people living with HIV (PLWH) as they age. There is no evidence regarding models of care. We aimed to assess feasibility of a novel methodology to investigate care processes for serious medical events in PLWH. Method: The method was based on the National Confidential Enquiry into Patient Outcome and Death (NCEPOD). Data were extracted from medical records and questionnaires completed by general practitioners (GPs), HIV physicians, and non-HIV specialist physicians. A panel reviewed anonymized cases and gave feedback on the review process. Results: Eleven of 13 patients consented to the study. Questionnaires were completed by 64% of HIV physicians, 67% of non-HIV specialist physicians, and 55% of GPs. The independent review panel (IRP) advised improvement in the methodology including data presentation and timing. Conclusion: This method was acceptable to patients and secondary care physicians. Further work is needed to the improve GP responses and facilitate IRP.